Efficacy and safety of risperidone long-acting injection in elderly people with schizophrenia - Dhiren Singh (Dove Medical Press, 2009)
Dhiren Singh1,2, Daniel W O’Connor11Department of Psychological Medicine, Monash University, Melbourne, Australia; 2Peninsula Mental Health Service, Melbourne, AustraliaAbstract: Antipsychotic medication is the mainstay of treatment in elderly patients with psychosis. In recent years, second generation antipsychotics have come to be preferred. Longacting risperidone is the first such antipsychotic available for use in this vulnerable group of patients and offers an attractive alternative to traditional medications. The available literature revealed that long-acting risperidone is generally well tolerated and is effective in treating both the positive and negative symptoms of schizophrenia. Despite a lack of randomized trials and head-to-head studies, it appears to be a useful addition to the treatment armory for patients with chronic psychosis who require a depot preparation. Further research into its endocrine and metabolic side effects is needed.Keywords: risperidone, long-acting injection, old age, efficacy, safety